2013
DOI: 10.1038/srep01153
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transition in IrTe2: A combined study of optical spectroscopy and band structure calculations

Abstract: Ir1−xPtxTe2 is an interesting system showing competing phenomenon between structural instability and superconductivity. Due to the large atomic numbers of Ir and Te, the spin-orbital coupling is expected to be strong in the system which may lead to nonconventional superconductivity. We grew single crystal samples of this system and investigated their electronic properties. In particular, we performed optical spectroscopic measurements, in combination with density function calculations, on the undoped compound … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

28
206
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(239 citation statements)
references
References 25 publications
28
206
4
Order By: Relevance
“…The spectral weight at E F gradually decreases with cooling from 300 to 260 K and to 100 K without losing the metallic E F feature as shown in Fig. 4e, consistently with the optical results across the HT to q 1/5 phase transition 14 . These results well explains the resistivity jumps across the transitions (see Fig.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The spectral weight at E F gradually decreases with cooling from 300 to 260 K and to 100 K without losing the metallic E F feature as shown in Fig. 4e, consistently with the optical results across the HT to q 1/5 phase transition 14 . These results well explains the resistivity jumps across the transitions (see Fig.…”
Section: Resultssupporting
confidence: 84%
“…IrTe 2 was reported as a new CDW material with a modulation vector q ¼ (1/5 0 1/5) below a CDW transition temperature T C B260 K and also as a mother compound of Ir based superconductors [11][12][13] . Various efforts have been conducted to elucidate electronic mechanisms of the charge modulation 11,13,14 , but the CDW like nature was disputable. A recent X-ray diffraction (XRD) study suggested charge modulations not only in the Te site but also in the Ir site with dimerization below T C 15 , suggesting a possibility of the Ir site CO.…”
mentioning
confidence: 99%
“…The inner Fermi surfaces observed around the A point at 300 K are roughly consistent with the prediction of band-structure calculations. 7,11) Figure 1(c) shows the Fermi surface mapping at 20 K well below the transition temperature. Across the structural transition, in the region where the outer Fermi surface is close to the inner Fermi surfaces, while the outer Fermi surface at 300 K is observed separately from the inner Fermi surfaces, the outer Fermi surface at 20 K disappears due to partial gap opening or overlaps with the inner Fermi surfaces.…”
mentioning
confidence: 99%
“…11) Fang et al conclude that the structural transition of IrTe 2 is not of CDW type but of a novel type driven by Te 5p holes. 11) In this context, it is very interesting and important to study the geometry of multi-band Fermi surfaces of IrTe 2 using angle-resolved photoemission spectroscopy (ARPES). In the present ARPES study, above the transition temperature, the flower-shaped outer Fermi surface and the inner Fermi surfaces like six connected beads, which are predicted by band structure calculations, are partly identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation